AN ANALYSIS OF STUDENTS’ BARRIERS IN READING SKILL AT SMPN 35 MAKASSAR - Aulia, Silvi; Batau, St. Haliah; Muliati, Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
The objective of the research was to find out what barriers students’ experience in reading skill of second grade students’ of SMPN 35 Makassar. This research method was a descriptive quantitative with a likert scale design. This research conducted in two steps, namely observation and giving questionnaire. There were 15 statements with used percentage of data frequency to calculated the questionnaire. This research was conducted on second grade students of SMPN 35 Makassar. The samples of this research consisted of 20 students of class VIII-5 for the 2023/2024 academic year. Researcher analyzing data from questionnaires distributed to students. The result of the research can be seen that barriers experienced by students in reading skill consist of self-confidence, students' interest and environment.